Facile preparation of Nd 2 Zr 2 O 7 –ZrO 2 nanocomposites as an effective photocatalyst via a new route - Zinatloo-Ajabshir, S.; Zinatloo-Ajabshir, Z.; Salavati-Niasari, M.; Bagheri, Samira; Hamid, Sharifah Bee Abd (Elsevier, 2017)
Nd2Zr2O7–ZrO2 nanocomposites were prepared via a facile process with propylene glycol as novel connecting agent and benzene tricarboxylic acid as a new complexing agent. The as-obtained Nd2Zr2O7–ZrO2 nanocomposites were characterized by transmission electron microscopy (TEM), UV–vis diffuse reflectance spectroscopy, energy dispersive X-ray microanalysis (EDX), Fourier transform infrared (FT-IR) spectroscopy, field emission scanning electron microscopy (FESEM), and X-ray diffraction (XRD). According to the morphological studies of the as-synthesized nanocomposites, it was found that the shape and particle size of Nd2Zr2O7–ZrO2 nanocomposites depended on the space-filling template type, dosage of space-filling template and tricarboxylic acid as complexing agent. Nd2Zr2O7–ZrO2 nanocomposites with different shapes and grain sizes have been synthesized. The photocatalytic behavior of as-produced Nd2Zr2O7–ZrO2 nanocomposites was also investigated through photodegradation of methylene blue dye and 2-naphthol as water pollutants.